1985
DOI: 10.1021/bi00329a036
|View full text |Cite
|
Sign up to set email alerts
|

Human leukocyte cathepsin G. Subsite mapping with 4-nitroanilides, chemical modification, and effect of possible cofactors

Abstract: The extended substrate binding site of cathepsin G from human leukocytes has been mapped by using a series of peptide 4-nitroanilide substrates. The enzyme has a significant preference for substrates with a P1 Phe over those with the other aromatic amino acids Tyr and Trp. The S2 subsite was mapped with the substrates Suc-Phe-AA-Phe-NA where AA was 13 of the 20 amino acid residues commonly found in proteins. The best residues were Pro and Met. The S3 subsite was mapped with the sequence Suc-AA-Pro-Phe-NA by us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
64
0

Year Published

1987
1987
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 45 publications
7
64
0
Order By: Relevance
“…Incubation of unlabelled ET-1 with purified cathepsin G allowed to identify a major cleavage site corresponding to the Hisl6-Leu x7 bond, leading to the formation of inactive [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] fragments and the C-terminal pentapeptide.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Incubation of unlabelled ET-1 with purified cathepsin G allowed to identify a major cleavage site corresponding to the Hisl6-Leu x7 bond, leading to the formation of inactive [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] fragments and the C-terminal pentapeptide.…”
Section: Discussionmentioning
confidence: 99%
“…This specificity is observed in the hydrolysis of the His-Leu bond of ET-1. The cleavage of this bond, generating [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] fragments and the C-terminal pentapeptide (Table I) is sufficient to induce a biological activity loss of ET-1. Indeed, we have previously shown that [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] peptides, resulting from the hydrolysis of ET-1 by endopeptidase 24.11, were devoid of vasoconstrictor effect on isolated rat aortic rings [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The enzyme cleaves predominantly after Phe, Ala or Leu, with a substantial prel'erence for Phe over the other two aromatic amino acids, Tyr and Trp [11].…”
Section: Discussionmentioning
confidence: 99%